Co-infection of Sweet Orange with Severe and Mild Strains of Citrus tristeza virus Is Overwhelmingly Dominated by the Severe Strain on Both the Transcriptional and Biological Levels - Fu, Shimin; Shao, Jonathan; Zhou, Changyong; Hartung, John S. (Frontiers in Plant Science, 2017)
Citrus tristeza is one of the most destructive citrus diseases and is caused by the phloem-restricted Closterovirus, Citrus tristeza virus. Mild strain CTV-B2 does not cause obvious symptoms on indicators whereas severe strain CTV-B6 causes symptoms, including stem pitting, cupping, yellowing, and stiffening of leaves, and vein corking. Our laboratory has previously characterized changes in transcription in sweet orange separately infected with CTV-B2 and CTV-B6. In the present study, transcriptome analysis of Citrus sinensis in response to double infection by CTV-B2 and CTV-B6 was carried out. Four hundred and eleven transcripts were up-regulated and 356 transcripts were down-regulated prior to the onset of symptoms. Repressed genes were overwhelmingly associated with photosynthesis, and carbon and nucleic acid metabolism. Expression of genes related to the glycolytic, oxidative pentose phosphate (OPP), tricarboxylic acid cycle (TCA) pathways, tetrapyrrole synthesis, redox homeostasis, nucleotide metabolism, protein synthesis and post translational protein modification and folding, and cell organization were all reduced. Ribosomal composition was also greatly altered in response to infection by CTV-B2/CTV-B6. Genes that were induced were related to cell wall structure, secondary and hormone metabolism, responses to biotic stress, regulation of transcription, signaling, and secondary metabolism. Transport systems dedicated to metal ions were especially disturbed and ZIPs (Zinc Transporter Precursors) showed different expression patterns in response to co-infection by CTV-B2/CTV-B6 and single infection by CTV-B2. Host plants experienced root decline that may have contributed to Zn, Fe, and other nutrient deficiencies. Though defense responses, such as, strengthening of the cell wall, alteration of hormone metabolism, secondary metabolites, and signaling pathways, were activated, these defense responses did not suppress the spread of the pathogens and the development of symptoms. The mild strain CTV-B2 did not provide a useful level of cross-protection to citrus against the severe strain CTV-B6.